Association between public health emergencies and sexual and reproductive health, gender-based violence, and early marriage among adolescent girls: a rapid review - Shruti Shukla; Jessy Amarachi Ezebuihe; Janina Isabel Steinert (BMC, 2023)
Abstract Background As COVID-19 continues to impact lives and livelihoods around the world, women and girls are disproportionately affected. Crisis situations and related response measures, such as lockdowns, school closures, and travel restrictions, often exacerbate the adversities and human rights violations faced by adolescent girls. We conducted a rapid review to synthesise evidence on the impact of public health emergencies (PHEs) related to gender-based inequalities among adolescent girls. Methods We systematically searched five major databases. Records were imported into the online screening tool Rayyan, and 10% of the records were triple screened for eligibility. We included qualitative, mixed-methods, and quantitative studies that assessed the relationship between PHEs and any of the following outcomes: (1) gender-based violence, (2) early/forced marriage, and (3) sexual and reproductive health. Due to the heterogeneity of included study designs, no meta-analysis was performed, and studies were summarised narratively. Findings Out the initial 6004 articles, 11 studies met our eligibility criteria. Five of these assessed the impact of natural disasters and six were focused on consequences of the COVID-19 pandemic. Seven studies focused on the impact of PHEs on gender-based violence, three focused on sexual and reproductive health, and only one study looked at early marriage. The main impacts highlighted by the studies included (1) increases in physical, psychological, and sexual abuse, (2) increase in the occurrence of teenage pregnancy, (3) poor menstruation hygiene management, and (4) occurrence of early marriages. Mechanisms underlying these impacts were PHE-specific response strategies like home confinement, closure of schools, the worsening of families' financial situation such as the inability to pay for school fees or day-to-day living costs, and the disempowerment of and increased workloads for adolescent girls. Conclusion Although evidence on the impact of COVID-19 on gender-based violence, sexual and reproductive health, and especially forced or early marriage of adolescent girls is limited, results from studies on other PHEs indicate that during crises, these detrimental outcomes are exacerbated. Findings from our review have important implications for policies and programs providing life skills training, financial literacy training, credit support, and safe spaces for adolescent girls.